The Mediating Role of Benefit Management for Sustaining the Performance of Infrastructure Projects - Khan, Asadullah (2022)
Benefit management is a valuable approach, promoted and supported by strategic management for maximizing organizational benefits. It has also been recognized as a means of improving project performance, though more research is needed to understand how it works. This research adds to the contemporary literature on public sector project management by studying the links between project governance, benefit management, and project performance from a developing country perspective. This study provides insights for project professionals who are working in government organizations for optimizing the benefits of investment. The study provides a reference to formulate strategies for managing and governing the performance of government-funded projects in developing countries like Pakistan. The research uses a positivist approach and quantitative design.